PENGARUH KADAR AIR AWAL KAYU JATI DAN SUHU CURING PEREKAT PADA KEKUATAN GESER SAMBUNGAN KAYU JATI (TECTONA GRANDIS) SECARA PEREKATAN - Sugiman, Sugiman; Hayyi Nu’man, Abdul; Sulistyowati, Emmy Dyah (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
Adhesively wood-wood bonded joint has been widely used in structural applications, however because wood is a hygroscopic material that absorbed water from environment, hence the absorbed water affects the joints performance. The objective of the paper is to investigate water absorbtion and desorbtion behaviour and the combined effect of absorbed water into the wood before being bonded and adhesive curing temperature on the shear strength of teak wood joints. The initial water content in the wood was 0%, 37%, and 54%, while the curing temperature was a  room temperature for 24 hours, 50°C for 6 hours, and 100°C for 3 hours. The water absorbtion behaviour of teak wood deviate from the Fick's law, however the desorbtion tends to follow the Fick's law. Moreover the rate of absorbtion is higher than the rate of desorbtion. At the same curing temperature, the increase of water content decreases the shear strength of the joints; however the decrease was compensated by increasing the curing temperature. Curing at a high temperature (100 oC) improves the joints strength in all moisture content studied and the failure of the joints occurs at the wood.